Eclia Test- Review - G.Nivedhita1 , M.P.Brundha2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Chemiluminescent immunoassay is a modification of standard enzyme immunoassay which is a biochemicaltechnique that has evolved to be used in recent times. Immunoassay is a diagnostic biochemical test usedto quantify an analyte or a specific substance from blood or other body fluids. Electrochemiluminescenceimmunoassay (ECLIA) is a new developing method to determine antibodies in human being’s bloodsample.this has evolved from various other immunoassay methods that were previously used for detectionof enzyme/antibody etc. The test takes place following three principles. Electrochemiluminescenceimmunoassay testing has been used to detect many markers such as typhoid, cardiac, tumor markers andvarious infectious diseases in in-vitro analysis. It is also frequently used in the detection of recombinantspecific treponemal antigens. Research articles were searched from search engines such as MeSH, pubMed,Core, Google Scholar, Cochrane etc. the time period considere was from 2000 - 2020 which is 20 years.Articles were studied and data were collected under different headings. In Spite of many advantages ofimmunoassays, they have some limitations. Immunoassays rely primarily on activity between analyteand the natural antibody, they may have more intrinsic imprecision than other methods used in medicineanalysis. Biological markers might produce false positive results and usage of viral markers is still not foundfor the process of electrochemiluminescence immunoassay test. Late night salivary cortisol concentration,an indicator of cushing’s syndrome, is detected using this test. This research provides in-depth knowledgeand awareness of electrochemiluminescence immunoassay tests and paves the way for better diagnosticmethods for the future.